Intermolecular Interactions between Eosin Y and Caffeine Using 1H-NMR Spectroscopy. (10th November 2013) - Okuom, Macduff O.; Wilson, Mark V.; Jackson, Abby; Holmes, Andrea E.
Abstract : DETECHIP has been used in testing analytes including caffeine, cocaine, and tetrahydrocannabinol (THC) from marijuana, as well as date rape and club drugs such as flunitrazepam, gamma-hydroxybutyric acid (GHB), and methamphetamine. This study investigates the intermolecular interaction between DETECHIP sensor eosin Y (DC1) and the analyte (caffeine) that is responsible for the fluorescence and color changes observed in the actual array. Using 1 H-NMR, 1 H-COSY, and 1 H-DOSY NMR methods, a proton exchange from C-8 of caffeine to eosin Y is proposed.